(untitled) (Fiep Bulletin - online, 2011)
The physical performance of teenage and young adult athletes is influenced by the volume of training, the level of the competitions besides other factors. Thus, this study aimed at verifying the cardiorespiratory endurance, the agility and the strength levels of a group of young footballers who participate of tournaments held by the Federação Mineira de Futebol in the categories Juvenile and Junior. The cardiorespiratory endurance was assessed by the Cooper test (walking or jogging in 12 minutes) while the shuttle run test was used as an indicator of agility. Strength was measured through tests of vertical and horizontal jumping. The average for the group of players in Cooper’s test allows us to classify them in the 5th category of aerobic capacity, i.e., "Excellent", however when the individual classification was done, it was observed that in fact 36.36% of players were in this category, while 22.72% were in the top category, i.e., "Superior". Furthermore 31.81% were found to be in the “Good” range and 9.09% in the “Mean” one. In the agility test of the players more than half (70.97%) were below the 50th percentile for age, a worrying result considering the importance of agility to footballers. The group presented unsatisfactory results, as compared to the literature, in both tests of strength, that is, 46.18 ± 5.05cm for vertical jump and 204 ± 0,14cm for standing long jump. The tests performed allow us to conclude that the group of players need to practice the physical qualities tested and that the analysis of individual values allows us to select those who really need more training.